Best Management Practices (BMPs): Perimeter Borders - Vivek Sharma; Kati W. Migliaccio; Brian Boman; Jemy Hinton; Kevin Hancock (EDIS)
This publication addresses perimeter borders as a best management practice. Written by Vivek Sharma, Kati W. Migliaccio, Brian Boman, Jemy Hinton, and Kevin Hancock, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised May 2021.